Clinical outcomes of acute myeloid leukemia patients relapsing after matched related donor and umbilical cord blood transplantation - Bejanyan, Nelli (Bone Marrow Transplant, 2014)
AML relapse remains the leading cause of transplant failure among Allo-SCT recipients. A single institution study was conducted on 348 patients with AML who received an Allo-SCT from an umbilical cord blood (UCB, 222) or HLA-matched related (RD, 126) donor between 2000–2011. Relapse after Allo-SCT occurred in 72 UCB and 32 RD transplant recipients. Three patients achieved CR after withdrawal of immune suppression with no further therapy. Fifty-two patients received intensive post-relapse therapy, defined as systemic chemotherapy (22 UCB, 7 RD), second Allo-SCT (9 UCB, 2 RD), or DLI ± systemic chemotherapy (0 UCB, 12 RD); of these, 25% achieved CR (21% UCB vs. 35% RD, p=0.16). Survival at 1 year after relapse was 22% for all patients (19% UCB vs. 28% RD, p=0.36). In multivariable analysis, post-relapse mortality was lower in patients receiving intensive therapy for relapse (HR=0.4; 95% CI 0.2–0.6, p<0.01) and higher in patients with peripheral blood blasts above the median (HR=3.8; 95% CI 2.2–6.6, p<0.01), active infection (HR=1.9; 95% CI 1.0–3.5, p=0.05), and non-infectious medical complications (HR=2.0; 95% CI 1.2–3.5, p=0.01). In conclusion, patients with AML relapsing after Allo-SCT who were in good enough clinical condition to receive intensive therapy had superior short-term survival.